(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The authors proposed active surgical tactics as "damage control" in traumatic liver injuries. The “damage control” method has been used in the SFRSCEMP since 2013 as the only method of saving the lives of patients with traumatic liver injuries. During 2013–2023, 140 patients with liver injury were operated on in the emergency surgery departments of the SFRNCEMMP. Of these, 19 (14.61%) patients with severe liver injuries of IV and V degrees of damage according to E.Moore. The effectiveness of multi-stage tactics was assessed by the level of mortality and the number of purulent-septic complications. The results of surgical treatment of 19 patients with massive liver damage, aged 17 to 50 years, were studied. The average age is 26 years. Of these, 11 men, 8 women. The average assessment of the severity of injuries on a scaleISS was 34 points (17-76), according to E.Moore IV and V degrees of injury. The mean blood loss was 2800 ml (1750-3850 ml). All patients underwent a multistage laparotomy with gauze (film) tamponade, the average number of operations per 1 person was 2.7 (2-5), suturing of the liver wound with tamponade (13), extensive hepatotomy and ligation of blood vessels (3), atypical resection (2 ), stitching of large main vessels with taponade (1). The average bed/day in the intensive care unit is 13 (3-16) and the average bed/day in the clinic is 25 (3-28). Mortality was 26.3% (5 out of 19), mainly purulent-septic complications and multiple organ failure. The use of the "damage control" technique helped to reduce the incidence of mortality from acute pathology of the abdominal organs by 26.3%.